(Non)Religious Coping with a Natural Disaster in a Rural U.S. Community. (3rd March 2021) - Abbott, Dena; Franks, Andrew; Cook, Corey; Mercier, Caitlin
Religious/spiritual (R/S) coping following natural disasters is associated with positive outcomes, leading to perceptions that the absence of R/S coping leads to negative outcomes among nonreligious individuals. However, little research explicitly explores the coping strategies of nonreligious individuals in response to natural disasters and traumatic events. The present study collected data from a sample of survivors of a natural disaster event (i.e., a tornado) to test the relationship between (non)religiosity/(non)spirituality, coping, psychological distress, and posttraumatic growth. Statistical models suggested that problem-focused coping facilitated posttraumatic growth and lower levels of psychological distress among people with lower levels of institutional religiousness and/or individual spirituality (consistent with predictions), but not among people at high levels of religiousness/spirituality (contrary to predictions). Participants with moderate levels of institutional religiousness reported more dysfunctional coping and higher levels of psychological distress, as predicted. Emotion-focused coping was associated with fewer depressive symptoms following trauma among participants with low levels of institutional religiousness. These data suggest a complex relationship between trauma, posttraumatic growth, distress, and coping among varying levels of (non)religiousness/(non)spirituality. This study is among the first to suggest that problem-focused coping in particular may promote positive psychological outcomes among nonreligious/nonspiritual people following a natural disaster or traumatic event. Implications of these data (i.e., for treatment of trauma) are discussed.